Mathematics Teaching Instrument Using Discovery Learning Model For Social Arithmetic Topic of Junior High School - Faizah, Nurul; Roza, Yenita; Kartini, Kartini (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research was done based on the limited availability of teaching instrument for mathematic class as part of teacher preparation on the implementation of National Curriculum 2013. This research aims to develop the mathematics teaching instruments which includes Lesson Plan (LP) and Student Worksheet (SW). Those instruments were developed based on discovery learning steps for teaching social arithmetic at Junior High School. The development research procedure is carried out with reference to the 4-D model developed by Thiagarajan which is done through the stage of define, design, develop and disseminate.Teaching instrumentswere validated by four validators and revised based on the suggestion of the validators. Researcher did two tested that are small group tested and large group tested. Researcher did the small tested for 10 students of SMPN 13 Pekanbaru to determine the validity of SW. Researcher also did the large group tested to 38 students of VII.10 SMPN 13 Pekanbaru for applying the LP and SW and getting respond from students. Based on data analysis of validator and studentsâ response it can be concludedthat the LP for social arithmetic is valid with score is 91.97% and the SW is very valid with the score is 89.40%. On Practicality aspects, SW had given score 95.70 % by student. Based on above score this teaching instrument is recommended to be used by the teacher in teaching topic social arithmetic for Junior High Students.